Rancang Bangun Aplikasi Jasa Pengiriman Paket Online Berbasis Android Pada PT Pos Indonesia - Purnawan, Yose; Suhandiah, Sri; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT Pos Indonesia is a state owned Enterprises which is engaged in courier, logistic, and financial transactions. The development of courier services and logistics balanced with the development of internet and smartphone technology. The development of internet and smartphone technology enables a new service opportunities to customer of PT Pos Indonesia that is design of online package shipment application based on android. The design of this application allows customer to make deliveries using android smartphone everywhere. Conclusion of the design of online package shipment application based on android is able to provide new services to customers of PT Pos Indonesia, which provide service feature such as package shipment anywhere without going to the post office, knowing their shipment orders for postal agency, and provide direction to courier post pickup shipment orders. Also generate customer report list, customer recap per province, package shipment list report, and payment report.